(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2026)
This article aims to explore the representations of travel discourse within the genre of maqama, taking the Baghdad Maqama by Ibn Mihraz al-Wahrani as a case study. The maqama is a narrative genre capable of incorporating various literary genres. The features of travel are clearly manifested in al-Wahrani’s maqama through the use of travel art characteristics such as narration, description, and the employment of the first-person pronoun (individual “I”), in addition to the diverse information contained within the maqama. The study concludes that the author, Ibn Mihraz al-Wahrani, successfully blended the genres of travel and maqama by drawing on the unique elements of each literary form.